2023
DOI: 10.1210/clinem/dgad465
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Combined Oral Contraceptive Pills in the Management of Polycystic Ovary Syndrome: A Systematic Review and Meta-analysis

Johanna Melin,
Maria Forslund,
Simon Alesi
et al.

Abstract: Context Polycystic ovary syndrome (PCOS) is affecting more than every tenth woman. Objective As part of the 2023 International PCOS Guidelines update, comparisons between combined oral contraceptive pills (COCP), metformin and combination treatment were evaluated. Data Sources Ovid Medline, Embase, PsycINFO, All EBM and CINAHL were searched. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…A very recent meta-analysis of 46 RCTs has been performed as a 2023 update of the “International Evidence-based Guidelines for the Assessment and Management of PCOS”, highlighting that metformin is superior to hormonal treatment in controlling the blood sugar, overweight, and lipid profile of PCSO subjects [ 207 , 208 ]. Therefore, metformin is considered a second-line treatment in PCOS that offers benefits for the management of menstrual and ovulatory disorders, hirsutism, and metabolic and cardiovascular disorders [ 209 , 210 ].…”
Section: Resultsmentioning
confidence: 99%
“…A very recent meta-analysis of 46 RCTs has been performed as a 2023 update of the “International Evidence-based Guidelines for the Assessment and Management of PCOS”, highlighting that metformin is superior to hormonal treatment in controlling the blood sugar, overweight, and lipid profile of PCSO subjects [ 207 , 208 ]. Therefore, metformin is considered a second-line treatment in PCOS that offers benefits for the management of menstrual and ovulatory disorders, hirsutism, and metabolic and cardiovascular disorders [ 209 , 210 ].…”
Section: Resultsmentioning
confidence: 99%
“…One review focusing on obesity concluded that evidence for the use of anti‐obesity agents (including metformin) for this indication was ‘very limited,’ identifying only 11 relevant trials (including a total of 996 participants with PCOS) with only four included in the meta‐analysis 15 . Another review focusing on the treatment of hirsutism based on 36 relevant trials concluded that the combined oral contraceptive pill was superior to metformin for women with a BMI <25 kg/m 2 , but that the evidence for this outcome in other BMI groups was of very low quality 16 . Another review focusing on lowering weight and testosterone levels with insulin sensitizers (metformin vs. PPARγ agonists) based on 13 randomized controlled trials (RCTs) involving 787 women concluded that metformin was superior to rosiglitazone and non‐inferior to pioglitazone 17 .…”
Section: Current Clinical Uses Of Metformin Beyond Type 2 Diabetesmentioning
confidence: 99%
“…Combination treatment with COCP and metformin may be beneficial in high metabolic risk groups, including women with BMI ≥30 kg/m 2 , and those with risk factors for type 2 diabetes (T2D). 13 Inositol is not recommended but can be considered based on individual preferences. Potential improvement in metabolic measures is noted, but with limited clinical benefits including in ovulation, hirsutism and weight.…”
Section: Manag Ement Of Nonfertilit Y Fe Atu R E Smentioning
confidence: 99%
“…Combination treatment with COCP and metformin may be beneficial in high metabolic risk groups, including women with BMI ≥30 kg/m 2 , and those with risk factors for type 2 diabetes (T2D) 13 …”
Section: Management Of Nonfertility Featuresmentioning
confidence: 99%